Genome-wide association study identifies variants in the ABO locus associated with susceptibility to pancreatic cancer - Amundadottir, Laufey (2009)
We conducted a two-stage genome-wide association study (GWAS) of pancreatic cancer, a cancer with one of the poorest survival rates worldwide. Initially, we genotyped 558,542 single nucleotide polymorphisms in 1,896 incident cases and 1,939 controls drawn from twelve prospective cohorts plus one hospital-based case-control study. In a combined analysis adjusted for study, sex, ancestry and five principal components that included an additional 2,457 cases and 2,654 controls from eight case-control studies, we identified an association between a locus on 9q34 and pancreatic cancer marked by the single nucleotide polymorphism, rs505922 (combined P=5.37 × 10-8; multiplicative per-allele odds ratio (OR) 1.20; 95% CI 1.12-1.28). This SNP maps to the first intron of the ABO blood group gene. Our results are consistent with earlier epidemiologic evidence suggesting that people with blood group O may have a lower risk of pancreatic cancer than those with groups A or B.